Dying Green A Journey through End-of-Life Medicine in Search of Sustainable Health Care - Vatovec, Christine (Critical Issues in Health and Medicine, 2023)
The slow violence being inflicted on our environment-through everything from carbon emissions to plastic pollution-also represents an impending public health catastrophe. Yet standard health care practices are more concerned with short-term outcomes than long-term sustainability. Every resource used to deliver medical care, from IV tubes to antibiotics to electricity, has a significant environmental impact. This raises an urgent ethical dilemma: in striving to improve the health outcomes of individual patients, are we damaging human health on a global scale? In Dying Green, award-winning educator Christine Vatovec offers an engaging study that asks us to consider the broader environmental sustainability of health care. Through a comparative analysis of the care provided to terminally ill patients in a conventional cancer ward, a palliative care unit, and an acute-care hospice facility, she shows how decisions made at a patient's bedside govern the environmental footprint of the healthcare industry. Likewise, Dying Green offers insights on the many opportunities that exist for reducing the ecological impacts of medical practices in general, while also enhancing care for the dying in particular. By envisioning a more sustainable approach to care, this book offers a way forward that is better for both patients and the planet